Following the money : the Wire and distant American studies - Cvek, Sven (Array, 2014)
In this essay, I argue that the pedagogical, or, more generally, heuristic potential of HBO’s crime drama The Wire (2002/2008) is related to the specific institutional developments in post- network television, the show’s didactic intention, and its focus on the delineation of the economic process, or what has been called its “openly class-based” politics. I will dedicate most time to the latter, as it represents a particularly welcome intervention for American Studies, a discipline in which the problem of class has usually been either marginalized, or articulated in terms of the historically hegemonic disciplinary paradigm, that of identity.